1996
DOI: 10.1111/j.1442-2042.1996.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of Adhesion and Endocytosis of Calcium Oxalate Crystals in Renal Tubular Cells

Abstract: The present investigation was designed to study the interactions between Madin-Darby canine kidney (MDCK) cells and calcium oxalate monohydrate (COM) crystals, the most abundant constituent of urinary crystals, and to clarify the significance of these crystal-cell interactions in stone pathogenesis. COM crystals adhered to the intact surface of MDCK cells by some biological mechanisms (biological adhesion) and, were then internalized into the cell (endocytosis). The microvilli of the cell appeared to play an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Lieske et al . [ 20] noted that microvilli appeared to play an important role in the adhesion and endocytosis of COM crystals, as also reported in our previous study [ 21]. Therefore, urine might have the potential to reduce crystal adhesion to cells by changing cell‐surface properties or microvilli function.…”
Section: Discussionsupporting
confidence: 78%
“…Lieske et al . [ 20] noted that microvilli appeared to play an important role in the adhesion and endocytosis of COM crystals, as also reported in our previous study [ 21]. Therefore, urine might have the potential to reduce crystal adhesion to cells by changing cell‐surface properties or microvilli function.…”
Section: Discussionsupporting
confidence: 78%
“…In 1992, Lieske, Walsh-Reitz, and Toback [18] reported that the internalization of calcium oxalate monohydrate crystals by African green monkey (BSC-1) and MDCK cells stimulated DNA synthesis. Hackett, Shevock, and Khan [19] subsequently found that crystal-containing MDCK and LLC-PK 1 cells were rapidly released from the cultures, which was confirmed in other studies [4,18,[20][21][22][23][24][25]. Koul et al [1,26] found that calcium oxalate monohydrate activates p38 mitogen-activated protein kinase (MAPK) in LLC-PK 1 .…”
Section: Discussionmentioning
confidence: 73%
“…Adhesion of COM crystals onto apical surface of renal tubular epithelial cells has been thought to be an early phase of stone nidus and kidney stone formation181920. Our previous expression proteomics study identified α-enolase as a COM crystal-binding protein on apical membranes of renal tubular epithelial cells by quadrupole time-of-flight (Q-TOF) tandem mass spectrometry (MS/MS)4.…”
Section: Discussionmentioning
confidence: 99%